COVID-19 vaccine knowledge and acceptance among the Libyan population: A cross-sectional study - Rana H. Shembesh; Mohammed S. Beshr; Mariam M. ALTarhouni (Human Vaccines & Immunotherapeutics)
We aim to identify Libyans’ knowledge, attitudes, and acceptance regarding the COVID-19 vaccine. A cross-sectional survey was electronically distributed to the Libyan population aged 18 and older between May and September 2023. The questionnaire had three sections: socio-demographics, COVID-19 vaccination and infection, and knowledge and attitudes toward the COVID-19 vaccine. The chi-square test was used to assess the associations. A total of 1,043 respondents completed the questionnaire. Of these, 590 (56.6%) were vaccinated, and 453 (43.4%) were unvaccinated. Only age, educational level, employment status, history of COVID-19 infection, and source of information had a significant association with vaccination status; all shared a p-value <.05. However, Monthly income did not. Regarding knowledge, 63.7% agreed that vaccines in general are an effective way to prevent and control infectious diseases, and 76.6% agreed that they can prevent disease and mortality. However, regarding COVID-19 vaccine, 48.4% agreed that the benefits outweigh the risks. Regarding COVID-19 safety, 40.8% responded that COVID-19 vaccines are only slightly safe or not safe at all. COVID-19 vaccine acceptance was at 57.2%, and only age and source of information were significantly associated. Those who held favorable views were more likely to accept the vaccine, while those who had concerns about safety were more vaccine hesitant. There is a gap between the perception of the COVID-19 vaccine compared to other vaccines among Libyans. Our study revealed that 57.2% of Libyans accept the COVID-19 vaccine. However, only 34% of the Libyan population is vaccinated. A comprehensive health policy is needed.